2014
DOI: 10.1371/journal.pone.0115135
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Variant in 12q13, a Possible Risk Factor for Bipolar Disorder, Is Associated with Depressive State, Accounting for Stressful Life Events

Abstract: Genome-wide association studies (GWASs) have identified a number of susceptibility genes for schizophrenia (SCZ) and bipolar disorder (BD). However, the identification of risk genes for major depressive disorder (MDD) has been unsuccessful because the etiology of MDD is more influenced by environmental factors; thus, gene–environment (G×E) interactions are important, such as interplay with stressful life events (SLEs). We assessed the G×E interactions and main effects of genes targeting depressive symptoms. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Because the heritability of MDD is low, but its prevalence is high, the pathophysiology of MDD is considered to be highly heterogeneous. Therefore, GWAS could not detect any genetic markers associated with the clinical risk of MDD (i.e., the effect size of markers was extremely small) because of insufficient statistical power ( 22 , 23 ). Because the meta-analysis of late-life depression was performed in only four studies ( n = 1,002), and the effect size of Val66Met for late-life depression was relatively high, we considered that this positive result might be a type I error ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the heritability of MDD is low, but its prevalence is high, the pathophysiology of MDD is considered to be highly heterogeneous. Therefore, GWAS could not detect any genetic markers associated with the clinical risk of MDD (i.e., the effect size of markers was extremely small) because of insufficient statistical power ( 22 , 23 ). Because the meta-analysis of late-life depression was performed in only four studies ( n = 1,002), and the effect size of Val66Met for late-life depression was relatively high, we considered that this positive result might be a type I error ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cause of heterogeneity might be the methodological quality of the studies, including age and gender matching and assay type (serum or plasma). Several researchers reported an absence of association between the BDNF gene and MDD, stating that the pathophysiology as well as diagnosis of MDD is extensively heterogeneous and, hence, it is very difficult to detect a susceptibility gene for MDD ( 4 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that the ‘core’ symptoms of PegIFN‐induced depressive state are different from those of the ‘general’ depressive state, which is usually associated with SLE. To clarify whether the core symptoms of PegIFN‐induced depressive state were unique, we compared the effect size (increase in subscale change between the baseline and worst point) for all BDI items between the current results and our previous cohort data (see Appendix S1 for details of our previous report of general depressive state) . In this explorative analysis, we found that ‘somatic symptoms’ (larger changes observed in the PegIFN therapy group, including sleep disturbance, loss of appetite, and weight loss) showed a relatively small effect size in our previous data for general depressive state (Table ).…”
Section: Resultsmentioning
confidence: 75%
“…However, interestingly, we identified a second peak for the onset of the depressive state in the later period of PegIFN therapy (after 20 weeks). Furthermore, we observed a different rate of SLE in depressive subjects between the two peaks: we speculate that the peak observed in the later onset of PegIFN therapy might not be due solely to the effect of PegIFN, but might also be influenced by SLE, which are definitive risk factors for general depressive state and depression . Presumably, PegIFN initiates the susceptibility for the development of a depressive state, and as a double hit, SLE induce depressive symptoms for subjects that develop a depressive state at later stages of therapy.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, there is genetic evidence linking D-serine with PTSD. A single nucleotide polymorphism (SNP; rs4523957) within the human serine racemase (SRR) gene previously associated with other disorders [55][56][57] , is a functional eQTL at the level of regulating SR mRNA expression in post-mortem human brain and is associated with PTSD 33 in a highly traumatized civilian population 58,59 .…”
Section: D-serine Mediated Nmdar Activation and Behaviormentioning
confidence: 99%